Kearifan Lokal Paseng Ri Ade’ dan Pemberdayaan Masyarakat Adat Karampuang dalam Upaya Pelestarian Hutan - Awaliyah, Nur Rezki; Hasriyanti, Hasriyanti; Maddatuang, Maddatuang (UNIVERSITAS NEGERI MAKASSAR, 2020)
This study aims to determine: 1) the role of paseng ri ade’ local wisdom in forest conservation efforts, 2) the form of preservation of indigenous peoples’ forest, 3) the form of empowerment of the Karampuang indigenous people in forest conservation efforts. This research is a qualitative descriptive study. Data collection techniques include observation, in-depth interviews with the selection of informants using purposive sampling, and documentation. Data analysis is done by examining all available data from various sources, namely the results of observations, interviews, field notes, documents. After that reduce data, expose data and conclusions. The results showed that 1) paseng ri ade’ was a source of informal rules applied to the Karampuang indigenous people so that they managed and utilized the forest using traditional practices. This form of preservation is the existence of a broad range of community rights in the utilization of forest products, has a certain way of taking forest products and behaving in accordance with applicable norms. 2)The form of forest preservation carried out by the indigenous Karampuang are, namely planting trees, reporting on violations, mainting karama’s forest and building permanent house. 3) Community empowerment carried out by the government, namely KBD (Village Seed Farming), community skills training, PRONA, ecotourism development, as well as involvement of traditional leaders in decision making at the village office.